Responses of Arbuscular Mycorrhizal Symbiosis to Abiotic Stress: A Lipid-Centric Perspective - Feng, Zengwei; Liu, Xiaodi; Zhu, Honghui; Yao, Qing (Frontiers in Plant Science, 2020)
Arbuscular mycorrhizal (AM) fungi are one of the most important soil microbial resources that help host plants cope with various abiotic stresses. Although a tremendous number of studies have revealed the responses of AM fungi to abiotic stress and their beneficial effects transferred to host plants, little work has focused on the role of lipid metabolism in AM fungi under abiotic stress conditions. AM fungi contain a large amount of lipids in their biomass, including phospholipids (PLs) in their hyphal membranes and neutral lipids (NLs) in their storage structures (e.g., vesicles and spores). Recently, lipid transfer from plants to AM fungi has been suggested to be indispensable for the establishment of AM symbiosis, and extraradical hyphae are capable of directly taking up lipids from the environment. This experimental evidence highlights the importance of lipids in AM symbiosis. Moreover, abiotic stress reduces lipid transfer to AM fungi and promotes arbuscule collapse as well as the hydrolysis and conversion of PLs to NLs in collapsed arbuscules. Overall, this knowledge encourages us to rethink the responses of AM symbiosis to abiotic stress from a lipid-centric perspective. The present review provides current and comprehensive knowledge on lipid metabolism in AM fungi, especially in response to various abiotic stresses. A regulatory role of abscisic acid (ABA), which is considered a “stress hormone”, in lipid metabolism and in the resulting consequences is also proposed.